Bina' Namat Al-Tafkir Al-Naqdii Bita’allum Al-Kutub Al-Shafro' Bishakli Manhajai Lithullaab Al-Madrasat Al-Diiniyah Bi Ma’had Al-Islamiah Al-Khoyrat Pagelaran Malang - Nasruddin, Muhammad Arif; A'yun, Qurroti (Lugawiyyat, 2025)
Studying and understanding the yellow book is a characteristic of learning at Salaf Islamic Boarding School, and one of the most famous  is the Bahtsul Masail culture  among students which shows that students are also trained and have a critical thinking pattern. From this phenomenon, this study aims to explain the learning methods applied to learning the yellow book at Madrasah Diniyah, Al-Khoirot Islamic Boarding School (Pondok Pesantren), Pagelaran Malang, and the critical thinking patterns of students. This research uses a qualitative approach with a descriptive method, data obtained through observation techniques, in depth interviews with teachers, students, and related parties at Madrasah Diniyah Al-Khoirot, and documentation. The result of this study is that the methods applied to learning the yellow book at Madrasah Diniyah Al-Khoirot are the Bandongan, Sorogan, and Bahtsul Masail methods. The three methods have different characteristics and goals, Bandongan is the most common and only involves students or learners as listeners, Sorogan is a method centered on students while teachers are proofreader, while Bahtsul Masail is the peak, requiring students to collect and study various literacy until testing their feasibility in a debate forum called Bahtsul Masail (Discussion of Various Problems). From these findings, it shows that the critical thinking pattern of students is well organized with various methods applied in Islamic Boarding School Al-Khoirot Pagelaran Malang.